2018
DOI: 10.11591/ijece.v8i3.pp1498-1512
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Digital Filter for Microprocessor Protection Relays

Abstract: The article considers some issues related to replacement of electromechanical relays used for protection of power facilities with microprocessor relays. One of the urgent problems connected with implementation of microprocessor overcurrent protections is how to use current transducers other than usual current transformers and in particular Rogowski coils that become more and more widespread. In the article are compared twelve methods of synthesis of a digital filter basing on the analog prototype -second-order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…To carry out experiments for mechanical testing of the welded joint quality, there were prepared samples from cast dispersion-hardened material poured into split steel molds. The welded joints of armor plates have some peculiarities [22,23], in particular, a butt joint is not used, notwithstanding, for the initial evaluation of the welded joint strength the butt welding method was applied. The tests have showed that the tensile strength directly depends on the joint welding method.…”
Section: Results Of Research and Their Analysismentioning
confidence: 99%
“…To carry out experiments for mechanical testing of the welded joint quality, there were prepared samples from cast dispersion-hardened material poured into split steel molds. The welded joints of armor plates have some peculiarities [22,23], in particular, a butt joint is not used, notwithstanding, for the initial evaluation of the welded joint strength the butt welding method was applied. The tests have showed that the tensile strength directly depends on the joint welding method.…”
Section: Results Of Research and Their Analysismentioning
confidence: 99%
“…In the ultraviolet area, there is a sharp rise in optical density to a maximum value at a wavelength of 650 nm, and the values gradually decrease in visible color and continue to decrease in the infrared area. Thus, we can consider this membrane as a neutral light filter with different optical densities for a wide range from the hard ultraviolet area to the soft X-ray with a high level of blocking of ultraviolet and visible background radiation [24,25].…”
Section: Resultsmentioning
confidence: 99%
“…Those that are based on classic circuit [2,3], symmetrical theories [4][5][6], digital wavelet transform (DWT) [4][5][6], and based on artificial neural network (ANN) [8,9]. The symmetrical theories and digital wavelet transform [4][5][6] require phasor estimation whose correctness depends highly on the efficiency of non-power frequency filtering [7]. The systems based on ANN [8,9] give satisfying results when it comes to classification tasks (fault type) but bad results when it comes to regression tasks (fault location).…”
Section: Introductionmentioning
confidence: 99%